Assistance protocol for venous ulcers patients: validation of contents - Daniele Vieira Dantas; Rodrigo Assis Neves Dantas; Isabelle Katherinne Fernandes Costa; Gilson de Vasconcelos Torres (Rev Rene, 2013)
Venous ulcers require complex treatment and are responsible for significant morbidity and mortality rates. This study aims at identifying aspects validated by the jury for the preparation of an assistance protocol for venous ulcer sufferers. It is a descriptive and quantitative research, with 39 professionals (30 nurses, 7 doctors and two physiotherapists), held at the Onofre Lopes University Hospital, between April and July/2010. Data collection began through a questionnaire checklist. Analysis was performed through Statistical Package for Social Science 15.0, assessing compliance with guidelines. Results were the compositional aspects of the protocol: assessment of patient and lesion history/documentation, wound care/perilesional skin, dressing suggestion, use of antibiotics and pain treatment, surgical treatment/medication, improving venous return and relapse prevention, patient referral, professional training and referral/counter-referral. It was concluded that to compose the protocol, aspects related to diagnosis, treatment and injury prevention must be considered.